IMPLEMENTATION OF THE MAIN DUTIES OF THE VILLAGE GOVERNMENT IN KADING VILLAGE TANETE RIAJA DISCTRICT BARRU REGENCY - Marsuki; Sri Tulhusna (P3M Stia Al Gazali Barru and Meraja media, 2022)
[Full Paper] to pdf Copyright (c) 2018 Meraja journal